2017
DOI: 10.1038/srep44792
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of IDH Mutation and Malignant Progression in Infiltrating Glioma

Abstract: Infiltrating low grade gliomas (LGGs) are heterogeneous in their behavior and the strategies used for clinical management are highly variable. A key factor in clinical decision-making is that patients with mutations in the isocitrate dehydrogenase 1 and 2 (IDH1/2) oncogenes are more likely to have a favorable outcome and be sensitive to treatment. Because of their relatively long overall median survival, more aggressive treatments are typically reserved for patients that have undergone malignant progression (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 46 publications
(53 reference statements)
10
56
0
2
Order By: Relevance
“…Notwithstanding this limitation, the IDH status is the primary determinant of glioma subtype classification (Louis et al , ) and interrogating the differences between IDHwt versus IDHm gliomas is essential to understand glioma biology. A key finding of our study is the major differences observed in phospholipid composition in IDHm gliomas, which is in line with recent observations made by MR spectroscopy (MRS) (Esmaeili et al , ; Jalbert et al , ). While MRS detects a signal from a pool of lipid molecules that resonate at the same frequency, while MSI can detect the distribution of specific metabolites that differ by their mass, which may explain differences obtained between the two approaches.…”
Section: Discussionsupporting
confidence: 92%
“…Notwithstanding this limitation, the IDH status is the primary determinant of glioma subtype classification (Louis et al , ) and interrogating the differences between IDHwt versus IDHm gliomas is essential to understand glioma biology. A key finding of our study is the major differences observed in phospholipid composition in IDHm gliomas, which is in line with recent observations made by MR spectroscopy (MRS) (Esmaeili et al , ; Jalbert et al , ). While MRS detects a signal from a pool of lipid molecules that resonate at the same frequency, while MSI can detect the distribution of specific metabolites that differ by their mass, which may explain differences obtained between the two approaches.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the anatomic lesion corresponding to a mixture of edema, gliosis, inflammation, and active tumor. Glu is the main neurotransmitter in the brain and has been found to be inversely correlated to the presence of isocitrate dehydrogenase (IDH) mutation, 10 and there was no difference in the levels of Glu/Cr and Glx/Cr. The levels of mI/Cr and mIG/Cr obtained from 3T short TE MRSI were statistically significantly higher in the T2 lesion than in the NAWM in patients with lower-grade glioma ( p = 0.002 and 0.015, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, most of the time ex vivo studies (i.e. high resolution magic angle spinning (HR‐MAS) of biopsies) are performed to confirm or explain changes seen in in vivo studies . However, interest in MRS(I) is increasing for clinical applications and research due to its ability to provide information about tissue spatial heterogeneity through collection of spectroscopic data and spatial distribution of metabolites, as well as their changes.…”
Section: Advantages Of Sampling the Metabolome By Mri/mrs(i)mentioning
confidence: 99%